A study of the role of neurotrophins in the mechanisms underlying the expression of long-term potentiation in the dentate gyrus - Casey, Marina (Trinity College (Dublin, Ireland). Department of Physiology, 2002)
Long-term potentiation (LTP) is a well-described form of synaptic plasticity. This study set out to investigate the role that tyrosine kinase plays in the expression of LTP at the perforant path-granule cell synapses of the rat in vivo and to determine the impact of neurotrophin-induced tyrosine kinase cascades.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin